Analysis Instagram Ads and Celebrity Endorsement to Purchase Intention on N95 Mask Product (Journal of Innovation, Business and Entrepreneurship, 2020)
There is a negative trend in the campus radio market. There are many reasons that suggest that the trend of campus radio is not good, such as a decrease in the popularity of campus radio in college advisory and university societies, a drop in the amount of direct institutional financial funding for college radio, an unavoidable move towards digital development and broadcast, changes in the composition of students involved in campus radio, and That mix makes it important for campus radio to make a leap in order to continue working. The goal of this research is to examine the motivation of campus radio listeners. Depending on the outcome, researchers will assess the motivation of campus radio listeners. The study used a quantitative approach through a questionnaire with a total of 110 respondents between the ages of 18 and 23, domiciled in Indonesia, and who are ITB students. The data where analyzed using a multi-linear regression method to identify the correlation. The study obtains four hypotheses from the literature review in the examination of the underlying motivation. Information, personal identity , social interaction and entertainment are the variables examined in this study. The outcome of the study showed information and entertainment has a significant correlation with the motivation of the campus radio listeners. This study is important to explain the behavior of listeners on the radio campus and to help marketers and program directors identify the best marketing and program approach. In fact, the results of the study could also improve and enhance the campus radio program based on identified variables in order to be more successful.Keywords: Motivation, Campus Radio, Community Radio, Uses and Gratifications, Environmental Friendly Attitudes.Keywords: Celebrity Endorsement , Instagram Ads , N95 Mask , Purchase intention, Social Media Marketing